1998
DOI: 10.1159/000028705
|View full text |Cite
|
Sign up to set email alerts
|

Psychopharmacologic Treatment of Acquired Attention Disorders in Children with Brain Injury

Abstract: This investigation examined the efficacy of psychostimulant therapy in alleviating neurobehavioral dysfunction attendant to pediatric brain injury. The most commonly reported neurobehavioral sequelae associated with head injury in the pediatric population involve deficits along the attentional matrix. This is also the most common objectively documented neurobehavioral finding among children as well as adults. There are several investigations in the adult literature which have employed the use of psychostimulan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 19 publications
3
51
0
Order By: Relevance
“…It is plausible that clinicians and parents perceived that ADHD symptoms would resolve in children who had no preinjury history of ADHD. In the absence of placebo-controlled, randomized clinical trials of pharmacologic treatment of the behavioral sequelae of TBI in children, the extant preliminary studies [22][23][24][25] provide only a suggestion that stimulants may be effective. With residual ADHD symptoms in our SADHD group and persistent high levels of symptoms in those children with preinjury ADHD, our results indicate the need for controlled treatment studies that stratify the randomization according to preinjury ADHD.…”
Section: Treatment With Stimulant Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is plausible that clinicians and parents perceived that ADHD symptoms would resolve in children who had no preinjury history of ADHD. In the absence of placebo-controlled, randomized clinical trials of pharmacologic treatment of the behavioral sequelae of TBI in children, the extant preliminary studies [22][23][24][25] provide only a suggestion that stimulants may be effective. With residual ADHD symptoms in our SADHD group and persistent high levels of symptoms in those children with preinjury ADHD, our results indicate the need for controlled treatment studies that stratify the randomization according to preinjury ADHD.…”
Section: Treatment With Stimulant Medicationsmentioning
confidence: 99%
“…8 The literature consists of a retrospective chart review of 10 children treated with methylphenidate after sustaining TBI and a crossover, placebo-controlled clinical trial. [22][23][24][25] In view of the findings of Mahalick et al 24 that methylphenidate produced cognitive gains over 1 week relative to placebo and performance with placebo did not differ from pretreatment baseline, there is justification for further clinical trials. Although the 2003 National Survey of Children's Health conducted by the Centers for Disease Control and Prevention 26 recorded that 56% of 4.4 million children age 4 to 17 years who had been diagnosed with developmental ADHD had been treated at some time with stimulants, and a recent population-based, birth cohort study 27 reported that 77% of children diagnosed with ADHD by DSM-IV criteria had been treated with stimulants by age 17 years, there are sparse data concerning the current practice of pharmacologic management of ADHD symptoms following TBI in children.…”
mentioning
confidence: 99%
“…Eight retrieved papers4 7 1621 evaluated MPH use after TBI. Five of these4 1619 met level 2b evidence criteria 22. No studies solely examined use of MPH with brain tumours as participants with ALL were always included.…”
Section: Commentarymentioning
confidence: 99%
“…Several prospective randomized controlled studies showed improvement of processing speed and inattention after brain injury with the use of methylphenidate (Mahalick et al, 1998;Plenger et al, 1996;Whyte et al, 2004;Whyte et al, 1997).…”
Section: Decreased Processing Speed and Distractibilitymentioning
confidence: 99%